(untitled) (Carte Romanze, 2015)
L’articolo si propone di considerare le somiglianze fra alcune vicende antico-francesi (l’Yvain di Chrétien de Troyes e il fabliau anonimo De celle que se fist foutre sur la fosse son mari) con una scena del Riccardo III di Shakespeare. Anche se non si può dire che il dramma inglese dipenda dai testi narrativi oitanici, esso sviluppa lo stesso motivo della vedova consolata e una serie di motivi secondarî, di immagini (il sangue, il diavolo, la seduzione) e di espressioni letterarie in modo sintomaticamente affine. The paper aims to evaluate similarities between some Old-French narratives (Chrétien de Troyes’ Yvain and the anonymous fabliau De celle que se fist foutre sur la fosse son mari) and a scene from Shakespeare’s Richard III. Although we cannot affirm that Shakespeare’s play derives from the French narratives, it develops the same theme of “comforted widow” along with a series of secondary themes, of images (the blood, the devil, the seduction) and literary expressions in a symptomatically, very similar way.